Implementasi Model Pembelajaran Kooperatif untuk Meningkatkan Keaktifan Siswa Kelas IX dalam Mata Pelajaran Pendidikan Agama Kristen [The Implementation of the Cooperative Learning Model to Increase Students' Activeness in a Grade 9 Biblical Studies Class] - Chindy Mutiara Br Hombing; Yanti Yanti (Universitas Pelita Harapan, 2023)
Students as beings created in the image of God have qualities that exceed other creatures, namely intellectual, social, and spiritual abilities that direct them to positive goals through their involvement in the learning process. Not only do they need to learn to listen to the teacher, but students are also expected to play an active role in their learning. In fact, the situation found indicate the tendency of student to only listen to the teacher's delivery, thus the learning is less interactive and collaborative. As a result, the learning atmosphere seems stiff and boring and even student does not have the opportunity to express their perspective on the learning material. This indicates the teacher's lack of attention to the existence of students as Imago Dei who have been specially equipped to experience the learning process. Thus, the problem of activity urges teachers to create an interactive learning atmosphere. The author proposes a method that can be applied, namely the cooperative learning model. The purpose of this study is to examine the results of the implementation of the cooperative learning model as an effort to increase student activity. The research method used is descriptive qualitative through a literature review of previous studies. The results of the implementation of the cooperative learning model can increase student activity measured based on three indicators of research success, namely student participation, social interaction and paying attention to teacher explanations in participating in learning. The author's suggestion for further research is to apply a cooperative learning model by using supporting methods such as role play and mind mapping to increase student activity.BAHASA INDONESIA ABSTRACT: Siswa sebagai ciptaan yang diciptakan menurut gambar dan rupa Allah memiliki kualitas yang melebihi ciptaan lainnya, yaitu kemampuan intelektual, sosial, dan spiritual yang mengarahkan siswa kepada tujuan yang positif melalui keterlibatannya dalam suatu proses pembelajaran. Siswa tidak hanya belajar dengan mendengarkan guru, tetapi siswa diharapkan dapat berperan aktif dalam pembelajaran. Kenyataannya, kondisi yang ditemukan menunjukkan adanya kecenderungan siswa hanya mendengarkan penyampaian guru sehingga pembelajaran kurang interaktif dan kolaboratif. Akibatnya, suasana pembelajaran terkesan kaku dan membosankan bahkan siswa tidak memiliki kesempatan untuk mengemukakan pendapatnya terhadap materi pembelajaran. Hal ini mengindikasikan kurangnya perhatian guru terhadap keberadaan siswa sebagai Imago Dei yang telah dibekali secara khusus untuk mengalami proses pembelajaran. Dengan demikian, masalah aktivitas mendesak guru untuk menciptakan suasana pembelajaran yang interaktif. Penulis mengajukan sebuah metode yang dapat diterapkan, yaitu model pembelajaran kooperatif. Sehingga tujuan penelitian adalah untuk mengkaji hasil penerapan model pembelajaran kooperatif sebagai upaya meningkatkan aktivitas siswa. Metode penelitian yang digunakan adalah deskriptif kualitatif melalui studi literatur terhadap penelitian-penelitian sebelumnya. Hasil penerapan model pembelajaran kooperatif dapat meningkatkan aktivitas siswa yang diukur berdasarkan tiga indikator keberhasilan penelitian, yaitu partisipasi siswa, interaksi sosial dan memperhatikan penjelasan guru dalam mengikuti pembelajaran. Saran penulis untuk penelitian selanjutnya adalah menerapkan model pembelajaran kooperatif dengan menggunakan metode pendukung seperti role play dan mind mapping untuk meningkatkan aktivitas siswa.